A22 PREVALENCE OF IRON DEFICIENCY AND SUPPLEMENTATION PRACTICES FOR PATIENTS ON HOME PARENTERAL NUTRITION. (4th March 2021) - Russell, L; Mangat, R; Plant, J; Hansen, S; Armstrong, D; Pinto-Sanchez, M I
Abstract: Background: Iron deficiency (ID) is common in patients receiving parenteral nutrition (PN), likely due to a lack of iron in the PN formula. There is no clear consensus on how often serum iron should be tested or iron supplementation should be given, at which dose or route, in patients on long-term PN. Within the Hamilton Health Sciences (HHS) home PN (HPN) program, the prevalence of ID or iron deficiency anemia (IDA) is unknown. This knowledge will contribute to better iron prescribing practices with ultimate benefit on patient's health. Aims: To assess the prevalence of ID and IDA in patients enrolled in the HHS HPN Program. The secondary aim was to assess supplementation practices for patients enrolled in the HPN program according to gastrointestinal(GI) diagnosis and duration on PN. Methods: We conducted a retrospective study including consecutive adult patients enrolled in the HHS-HPN program from January 2015 to November 2020. We collected data on demographics (age, sex, and GI diagnosis), iron supplementation (dose, duration, and route), and information related to iron-deficiency (hemoglobin, serum iron, ferritin, TIBC, and folate) at pre-set intervals (enrollment, 3, 6, 12, 18, 24, 30, 36, 48, 60 months) and last measured. ID was defined as ferritin ≤45μg/L or serum iron ≤9μmol/L. IDA was defined as hemoglobin <130g/L in men or <120g/L in women in the context of ID. Data were expressed as median (IQR) for continuous variables and n/N(%) for categorical variables. Chi 2 was performed to assess differences between groups and logistic regression to assess predictors of ID and IDA. The analysis was conducted using SPSS software(v26). Results: The analysis included 125 HPN patients (50 males, median age of 55 (40–65) years). Patients received PN for a median of 195 (83–521) days. The most common diagnoses were malignancy (36.8%) and inflammatory bowel disease (23.2%); the most common indications for HPN was short bowel (29.6%) and bowel obstruction (27.2%). Iron profiles were measured in 77% of patients. At enrollment, 42.2% of patients had ID and 38.9% had IDA. Only 13% of patients with ID and 22.8% with IDA had iron supplementation (Figure 1). A total of 38 patients received iron either oral or IV (oral=44.7% vs IV=55.3%; p=0.66). There was no correlation between low levels of serum iron or ferritin with iron supplementation (p=0.23, 0.45 respectively). Age, sex, diagnosis, or reason for PN did not correlate with ID or IDA at any time point. Conclusions: Iron-deficiency and IDA are common in patients enrolled in the HHS HPN program independently of age, sex, diagnosis and reason for PN. Prospective studies are needed to implement the most effective way to ensure proper monitoring and treatment of iron deficiency in this population. Funding Agencies: None